Fines effect on gas flow in sandy sediments using μCT and pore networks - Jamal A. Hannun (14779078) (2022)
Gas production from hydrate-bearing sediments requires methane dissociation, which induces two-phase gas flow, mobilizing fine clay particles from within saturated pores. Fines migration within sandy sediments results in subsequent pore clogging, reducing reservoir connectivity. Sediments complex pore morphology, require direct 3D microscopic pore-scale imaging to investigate fines' influence on the porous media. The work uses synchrotron microcomputed tomography, to understand how fines migration due to gas injection, affects pore morphology and gas connectivity within sandy sediments. The goal is to study the impact of fines type and content at different gas injection stages, on gas flow regime and sediments rearrangement. Six saturated samples of sand and fines mixtures (Kaolinite and Montmorillonite at different contents) underwent four stages of gas injection during in-situ 3D scanning. X-ray images were segmented for direct visualization, as well to quantify gas ganglia distribution, also to extract pore networks to statistically measure changes in pore and throats distributions, and to simulate single-phase and relative permeability. Findings reveal that the extent of deformation to pore morphology increases with fines content and gas injection regardless of fines type. High kaolinite content (equal to or larger than 6%) results in fractured porous media, while high montmorillonite content (equal to or larger than 5%) results in disconnected vuggy media. Lower contents cause a gradual reduction in pore and throat sizes during gas injection. As fines content increases, clogging intensifies, thus gas connectivity and flow regime changes from connected capillary to disconnected vugs and microfractures. Both hydrophobic and hydrophilic fines reduced throat sizes, due to dislocations in sand grains. A unique pattern is discovered using pore networks, which describe pore-size fluctuations during fractures and vugs formation, due to fines migration. Other Information Published in: Journal of Natural Gas Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jngse.2022.104834